Effect Alkali Immerse Duration and Fiber Weight Fraction of Artocarpus Elasticus Bark Fiber Composites on Impact Strength for Mudguard Material - Mirza Hylmi Zhafif Lukito; Etik Puspitasari (JURAL RISET RUMPUN ILMU TEKNIK, 2025)
Composite materials are produced by combining two or more different materials, to achieve mechanical properties superior to those of the individual components. One example of a natural fiber-based composite is the composite made from the skin fiber of the lantung wood (Artocarpus elasticus). This study aims to analyze the effect of alkali immerse durations (60 minutes, 90 minutes, and 120 minutes) and fiber weight fractions (5%, 10%, and 15%) on the impact strength of the composite, using lantung wood bark fibers as the control due to their inherent mechanical strength. The experiment was conducted by varying the independent variables, such as alkali immerse duration and fiber weight fraction, and dependent variables including fiber orientation and NaOH concentration (horizontal orientation, 10%). The research method used in this research is design of experimental (DOE) method. Impact testing was performed using a Charpy impact tester, and the resulting data were analyzed quantitatively to evaluate the relationships among the variables. Although the benefits of natural fibers are well-known, there is still a lack of empirical data regarding the effects of alkali immerse duration and fiber weight fraction on the impact strength of the composites. The study purpose is to fill this gap by systematically analyzing the effects of alkali immerse duration and fiber weight fraction on the mechanical performance of lantung wood bark fiber-based composites. The research result show that a 120-minute immerse duration yields an impact value of 0.029 J/mm², while a 10% fiber weight fraction results in an impact value of 0.033 J/mm². The research contributes to the optimization of fabrication parameters, particularly in the automotive sector, such as in the production of lightweight components like rear wheel mudguard for motorcycles.